INDUSTRIAL LAWS RELATING TO WOMEN LABOUR FORCE IN INDIA: A STUDY - Khandare, Jayashree; Sinha, Shivangi (International Journal of Psychosocial Rehabilitation, 2020)
Despite the enactment of several legislations in India, women at workplace continue to encounter numerous problems. One of the central problems faced by women at workplace is that of inequality in wages and discrimination on the ground of sex. History bears witness to the fact that such problems have existed for decades together, consequent of which several legislations, which include the Maternity Benefits Act, 1961 and the Equal Remuneration Act, 1976 were enacted. The same was in line with and in realization of the constitutional ideal of equality and in consonance with provisions that direct the State to incorporate protective, beneficial and health provisions in the various enactments. This paper is an exploratory study of legislations catering to the needs of women in workplace.